Use of a 416B-type central-hybrid experimental design to evaluate the synthesis conditions of TiO2/biochar composites on the solid-state photocatalytic degradation of polypropylene-plastic films (2025)
This study presents an innovative application of solid-state photocatalysis using environmentally friendly TiO2/biochar composites to degrade polypropylene (PP) films and reduce plastic pollution. Biochar, derived from coconut shells via controlled pyrolysis, was combined with TiO2 to enhance photocatalytic activity. A 416B-type Central-Hybrid Experimental Design was used to optimize synthesis parameters, revealing that biochar produced at 280°C with 4.1 % v/v oxygen and a TiO2/biochar weight ratio of 1.5 yields the best results. After 25 days of UV irradiation, films incorporated with TiO2/biochar composites exhibited an 8.7 % weight loss and a carbonyl index of 11.4—significantly surpassing pristine PP films. These findings demonstrate the potential of biochar as a sustainable solution to reduce nanotoxicity while boosting polymer degradation efficiency. This work contributes to the development of eco-friendly materials for mitigating plastic waste challenges.